2013
DOI: 10.1016/j.clbc.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Neoadjuvant Chemotherapy on HER2/neu Status in Invasive Breast Cancer

Abstract: Neoadjuvant chemotherapy for breast carcinoma resulted in the HER2/neu status alteration by IHC, but they have stable gene amplification status by FISH. HER2/neu protein overexpression indicated greater sensitivity to neoadjuvant anthracycline- and taxane-based chemotherapy. Thus, retesting HER2/neu IHC status in residual tumors after NAC should be considered in order to optimize adjuvant systemic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 43 publications
2
21
0
1
Order By: Relevance
“…Some studies that used IHC to measure HER2, HER2 status changed in 7.6% to 30.0% of tumors after NCT. 8,[18][19][20][21][22][23][24][25][26] A prospective study that used gene amplification to determine HER2 status found that up to 43% of trastuzumab-treated patients had tumors that had HER2 status discordance after NCT. 27 Similarly, we found that 45.7% of the trastuzumab-treated tumors became HER2-negative.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that used IHC to measure HER2, HER2 status changed in 7.6% to 30.0% of tumors after NCT. 8,[18][19][20][21][22][23][24][25][26] A prospective study that used gene amplification to determine HER2 status found that up to 43% of trastuzumab-treated patients had tumors that had HER2 status discordance after NCT. 27 Similarly, we found that 45.7% of the trastuzumab-treated tumors became HER2-negative.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with a non‐pathologic complete response (non‐pCR) have poorer outcomes than those with a pathologic complete response (pCR) . Because trastuzumab is used in NAC setting, changes in the HER2 status of surgical specimens have been reported . However, the incidence of HER2 discordance between before (in needle biopsy specimens) and after chemotherapy (in surgical specimens), and the prognostic impact of such discordance remain unclear .…”
Section: Introductionmentioning
confidence: 99%
“…Neoadjuvant therapy is mainly based on the immunohistochemical findings of the HR and HER2 status on the core needle biopsy. With the growing use of neoadjuvant therapy, it is important to know whether it modulates the biological behaviors of breast cancer cells [3, 23, 24]. …”
Section: Discussionmentioning
confidence: 99%